THE CONTRIBUTION OF DIGITAL PROFESSIONAL LEARNING COMMUNITY ACTIVITY STAGES TO TEACHER LEARNING PERFORMANCE COMPONENTS IN JAKARTA HIGH SCHOOLS - Hastuti, Rita; Permana Johar; Taufani, Taufani; Bakari, Abu (Conciencia, 2024)
This study aims to analyse the contribution of digital Professional Learning Community (PLC) activity stages to the components of teacher learning performance in Senior High Schools (SMA) in DKI Jakarta. The three aspects of performance studied include: teacher learning performance (jargu), peer learning (jarse), and professional development (karpro). This study used a quantitative method with multiple regression design, involving 133 teachers from seven schools in five areas of Jakarta. The analysis showed that the implementation stage of digital PLC contributed the most to teachers' learning performance by 58.7%, while evaluation affected professional development by 58.2%, and planning contributed to peer learning by 40.6%. Overall, the regression model shows that all the variables of the digital PLC activity stages simultaneously have a significant positive effect on improving teacher learning performance, with a coefficient of determination of 79.2%. These findings highlight the importance of school support in facilitating digital PLC activities to improve teaching quality and teacher professionalism.